A Meta-Model-Based Approach for Specification of Graphical Representations - Tveit, Merete (Electronic Communications of the EASST, 2009)
Meta-models are widely used for the specification of the international structure of graph modelling languages, and well-established standards (e.g. MOF) exist for this. For the graphical representation there is not the same agreement and no related standards. This paper presents a new meta-langauge for an independent specification of graphical representations. A diagram from the domain-specific language Service is used as a running example to show how this meta-model-based approach is appropriate for specifying the graphical representation in a precise way, but still on a high level of abstraction.